(untitled) (Multidisciplinary Journal of Science and Technology, 2026)
This article covers the theoretical and practical aspects of the methodology for improving the thinking skills of preschool children. The importance of pedagogical technologies, didactic games and interactive methods in the development of logical, independent and creative thinking in children is analyzed. Also, effective methods for developing thinking activity in the educational process, taking into account the age characteristics and individual abilities of children, are indicated. The article also presents methodological recommendations that can be used in preschool educational organizations.